Does lowering housing provident fund contribution rate promote employment? - Jue Tang (China Economic Quarterly International, 2022)
The housing provident fund is an important part of payroll taxes. This paper quantifies its impact on employment. Although the fund helps enterprises with R&D to recruit more employees, it will also reduce the profitability of enterprises and cause enterprises to shrink their production scale, resulting in a negative overall effect on the number of employees. The negative impacts are significant in groups with strong financing constraints, and it mainly affects workers with a low education level and male workers. This paper also examines the impact of the increase and decrease of the contribution rate. The results show that reducing the contribution rate will promote employment.